2018
DOI: 10.1002/smi.2843
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood stressors and psychological distress among U.S. Latinos: Measuring the protective effects of social support from family and friends

Abstract: We examined whether social support from family and friends, separately, reduce the deleterious effect of neighborhood stressors on psychological distress among Latinos by subgroup. Utilizing data from a nationally representative sample of 2,524 Latinos (National Latino and Asian American Survey), we found that neighborhood stressors were associated with higher distress among people with low and average levels of family support, although there was no significant association between neighborhood stressors and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 65 publications
0
21
0
Order By: Relevance
“…In addition, we find that associations between social support and mental health vary between different social support types. Following existing studies, this study suggests that support from family and friend are helpful in against depressive symptoms and PTSD symptoms, 33 , 34 family support in particular. 35 However, this study observes that greater social support from other sources correlates with greater mental health symptoms.…”
Section: Discussionmentioning
confidence: 58%
“…In addition, we find that associations between social support and mental health vary between different social support types. Following existing studies, this study suggests that support from family and friend are helpful in against depressive symptoms and PTSD symptoms, 33 , 34 family support in particular. 35 However, this study observes that greater social support from other sources correlates with greater mental health symptoms.…”
Section: Discussionmentioning
confidence: 58%
“…Given that many Latinos place a high value on family, the strong association between family and mental health among this population has been well documented (Bostean, Andrade, & Viruell-Fuentes, 2019; Edwards & Lopez, 2006; Smokowski & Bacallao, 2007), and strong family bonds have been shown to have a protective role against the effects of stress on mental health among Latino populations (Raffaelli et al, 2013). For example, research examining a large representative Latino sample in the United States revealed that family cohesion, a unique dimension of family dynamics that describes the emotional bonding family members have toward one another (Olson, Russell, & Sprenkle, 1983), was associated with lower psychological distress (Rivera et al, 2008).…”
Section: Family Dynamics Mental Health and Discriminationmentioning
confidence: 99%
“…The perception that social support from family members and friends would be available if needed helps mental health because it softens the appraisal of the situation and prevents the cascading of negative stress responses ( Kawachi and Berkman, 2001 ). Family support is more important than friend support in reducing the deleterious effect of stressors on psychological distress ( Bostean et al., 2019 ). During the COVID-19 lockdown it is found that lower satisfaction with the support from the family may lead to higher self-reported distress ( Losada-Baltar et al., 2020 ).…”
Section: Distress Associated With Covid-19mentioning
confidence: 99%